Demand Systems With and Without Errors - Lewbel, Arthur (American Economic Review, 2001)
Revealed preference theory assumes that each consumer has demands that are rational, meaning that they arise from the maximization of his or her own utility function. In contrast, econometric or statistical demand models assume that each consumer's demands equal a rational systematic component derived from a common utility function, plus an individual-specific, additive error term. This paper reconciles these differences, by providing necessary and sufficient conditions for rationality of statistical demand models given individual consumer rationality. (JEL D11, D12, C30, C43)